Efeitos da inclinação da esteira na marcha de indivíduos hemiparéticos crônicos - Moreno, Cinthia de Carvalho (2009)
Objective: To examine the effects of treadmill inclinations on the walking of hemiparetic chronic subjects. Design: Observational descriptive study. Location: Laboratory of human movement analysis. Participants: Eighteen subjects, 10 men and 8 women were evaluated, with a mean age of 55.3 ± 9.3 years and the time since the injury of about 36 ± 22.8 months. Intervention: Not applicable. Main Outcome Measures: All subjects were evaluated for functional independence (Functional Independence Measure - FIM) and balance (Berg Balance Scale). Angular variations of the hips, knees and ankles in the sagittal plane were observed, as well as the speed of the movement (m/s), cadence (steps/min), stride length (m), cycle time (s), step time on the paretic leg and on the non-paretic leg (s), support phase time and balance phase time on the paretic leg (s) and the ratio of symmetry inter-limb as subjects walked on a treadmill at three conditions of inclination (0%, 5% and 10% ). Results: There were angular increases in the initial contact of the hip, knee and ankle, amplitude increase in the hip between 0% and 10% (37.83 ± 5.23 versus 41.12 ± 5.63, p < 0,001) and 5% and 10% (38.80 ± 5.96 versus 41.12 ± 5.63, p = 0,002), amplitude increases in the knee between 0% and 10% (47.51 ± 15.07 versus 50, 30 ± 12.82, p = 0,040), extension decreases in the hip, dorsiflexion increases in the balance phase and in the time of support phase from 0% to 5% (0.83 ± 0.21 versus 0.87 ± 0, 20, p = 0,011) and 0% and 10% (0.83 ± 0.21 versus 0.88 ± 0.23, p = 0,021). Conclusion: The treadmill inclination promoted angle changes as such as the increase of the angle of the hip, knee and ankle during the initial contact and the balance phase and the increase of the range of motion of the hip and knee; furthermore, it also promoted the increase of the support time of the paretic lower limb